Assessment of fresh and preserved amniotic membrane for guided bone regeneration in mice. Issue 10 (2nd May 2020) - Fenelon, Mathilde; Etchebarne, Marion; Siadous, Robin; Grémare, Agathe; Durand, Marlène; Sentilhes, Loic; Torres, Yoann; Catros, Sylvain; Gindraux, Florelle; L'Heureux, Nicolas; Fricain, Jean‐Christophe
Abstract: Thanks to its biological properties, the human amniotic membrane (HAM) can be used as a barrier membrane for guided bone regeneration (GBR). However, no study has assessed the influence of the preservation method of HAM for this application. This study aimed to establish the most suitable preservation method of HAM for GBR. Fresh (F), cryopreserved (C) lyophilized (L), and decellularized and lyophilized (DL) HAM were compared. The impact of preservation methods on collagen and glycosaminoglycans (GAG) content was evaluated using Masson's trichrome and alcian blue staining. Their suture retention strengths were assessed. In vitro, the osteogenic potential of human bone marrow mesenchymal stromal cells (hBMSCs) cultured on the four HAMs was evaluated using alkaline phosphatase staining and alizarin red quantification assay. In vivo, the effectiveness of fresh and preserved HAMs for GBR was assessed in a mice diaphyseal bone defect after 1 week or 1 month healing. Micro‐CT and histomorphometric analysis were performed. The major structural components of HAM (collagen and GAG) were preserved whatever the preservation method used. The tearing strength of DL‐HAM was significantly higher. In vitro, hBMSCs seeded on DL‐HAM displayed a stronger ALP staining, and alizarin red staining quantification was significantly higher at Day 14. In vivo, L‐HAM and DL‐HAM significantly enhanced early bone regeneration. One month after the surgery, only DL‐HAM slightly promoted bone regeneration. Several preserving methods of HAM have been studied for bone regeneration. Here, we have demonstrated that DL‐HAM achieved the most promising results for GBR.